Faktor-Faktor yang Mempengaruhi Pajak Pertambahan Nilai pada PT. Unilever Indonesia Tbk - Agustin Adi Yuliyanti; Sri Dwi Estiningrum (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This research aims to determine the factors that can affect the value added tax such as inflation, interest rates, and the value of exports at PT. Unilever Indonesia, Tbk. Research with a quantitative approach with secondary data types, namely periodic data (time series). The population of this research is the company's financial statements PT. Unilever Indonesia, Tbk for the period of the quarter or quarter in the period 2006-2020 or 15 years with a sample of 60 data. Furthermore, the data were analyzed using multiple linear regression assisted by SPSS Version 26 program. The results showed that interest rates and export values ​​had no effect on value added tax, while inflation had a significant effect on value added tax. Even though inflation can increase VAT through selling prices, but inflation that is too high can reduce people's purchasing power so that company sales will decrease, thus this can indicate to PT Unilever Indonesia, Tbk and also other companies that there is a need for detailed supervision of the supply chain. When inflation occurs, the company is advised to continue to produce in the amount it should and the sales chain such as distributors and retailers to continue to distribute normally, this aims to avoid product shortages and continue to increase inflation. In addition, the government is required to manage inflation effectively and efficiently so that the production strategy is not disrupted by price increases.